Deradicalization of Terrorism with a Progressive Humanist Approach - Muchamad Maskyur Alkhuseri; Suteki Suteki (Wacana Hukum, 2020)
Terrorism is an issue that has always been a concern of the international world. Because, no country in the world can be free from the threat of terror. To prevent and eradicate terrorism, de-radicalization is carried out. Implementation of de-radicalization can take the form of efforts to identify, rehabilitate, re-educate, and re-socialize for individuals or groups of people who are affected by radical beliefs by promoting the principles of empowerment, human rights, rule of law and equality. The writing of this research uses a qualitative conceptual approach. De-radicalization approach can be done more humanist to avoid the wide effect and could right on the target with the involvement of former terrorism to approach over the other former terrorists or terrorists to get their awareness back. De-radicalization using this method is more effective because former terrorists are more acceptable rather than other people.